2008
DOI: 10.1021/es702797b
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Lead Oxide (PbO2) by Iodide and Formation of Iodoform in the PbO2/I/NOM System

Abstract: Lead oxide (PbO2) can be an important form of lead mineral scale occurring in some water distribution systems. It is believed to be formed by the oxidation of lead-containing plumbing materials by free chlorine. Its reactivity in water, however, has not been well studied. Iodide is also found in source drinking waters, albeit at low concentrations. Consideration of thermodynamics suggests that iodide can be oxidized by PbO2. In this investigation, iodide ion was used as a probe compound to study the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 34 publications
5
72
1
Order By: Relevance
“…Anschutz et al (2000) proposed manganese oxides (MnO 2 ) and nitrate as possible electron acceptors in the oxidation of iodide to iodine and/or iodate based on the observed coupling of N, Mn, and I redox cycles in marine sediments. Lin et al (2008) also demonstrated that I À may be oxidized by lead oxide (PbO 2 ) in Pb-containing systems. From Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Anschutz et al (2000) proposed manganese oxides (MnO 2 ) and nitrate as possible electron acceptors in the oxidation of iodide to iodine and/or iodate based on the observed coupling of N, Mn, and I redox cycles in marine sediments. Lin et al (2008) also demonstrated that I À may be oxidized by lead oxide (PbO 2 ) in Pb-containing systems. From Fig.…”
Section: Introductionmentioning
confidence: 96%
“…However, concentration of IF, IAA and TIAA kept increasing from 4 h to 3 days while HOI and I 2 concentration decreased from 1 h to the end of reaction (Fig. 1), which implied that other reaction mechanism played a significant role in the formation of IF, IAA and TIAA, such as reaction of I 3 − with NOM [16].…”
Section: Effect Of Reaction Time On I-dbps Formationmentioning
confidence: 94%
“…Many studies reported that formation of I-DBPs during oxidative treatment of iodide-containing waters using chlorine [5][6][7]12,13], chloramines [5,13,14], ozone [13], manganese dioxide [15] and lead oxide [16]. However, few literatures specifically addressed the formation of iodinated organic compounds when treating iodidecontaining waters with potassium permanganate (KMnO 4 ), which is an oxidizing agent widely used throughout water industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOCl + OCl À ), a widely used disinfectant in distribution systems, provides a high ORP that favors PbO 2 formation [1,5,6]. The presence of reductants that include natural organic matter (NOM), Br À , I À , Mn 2+ , and Fe 2+ significantly enhanced the dissolution of PbO 2 [7][8][9][10][11][12][13]. The reductive dissolution of PbO 2 by water itself is even thermodynamically favorable [8,14].…”
Section: Introductionmentioning
confidence: 99%